Terrorism and societies - Vertigans, Stephen (Ashgate, 2008)
Terrorism yesterday and today : an introduction -- National Islamic terrorism : groups in the Palestinian territories -- International Islamic terrorism : al-Qaeida and related groups -- Republican and loyalist terrorism in northern Ireland -- Red urban terrorism : experiences in Italy, Germany, and Japan -- From left to right : terrorism within America from the 1960s -- Conclusion: Yesterday, today and tomorrow